Injury rates in Iranian taekwondo athletes; a prospective study - Ziaee, V.; Rahmani, S. -H.; Rostani, M. (Asian Journal of Sports Medicine, 2010)
Purpose: Taekwondo, as the most popular martial art among Iranian sportsmen, might lead to injury for the athletes of this sport during competitions. We decided to report the incidence rate of injuries sustained by the athletes of this sport during national competitions. Methods: All competitions of Iran national championship taekwondo league in 2006-2007 with 204 athletes were observed prospectively to detect the occurrence of injuries. The severity of injuries was classified into four groups (mild, moderate, severe, and critical) according to the involvement of medical care team in the contest, ability of the athletes to resume and duration of probable absence of injured athletes from future competitions and training sessions. Athlete-Exposure (A-E) was defined as the number of competitions multiplied by two. On this base, the rate of injury incidence per 1000 A-Es, the rate of injuries per time unit and the rate of injury occurred for each 100 athletes were considered as the major outcomes of this study. Results: Of totally 1,338 A-Es, 93 injuries were recorded during the competitions. The rate of injury incidence was found to be 69.5 injuries per 1000 A-Es and the rate of injuries per minute of competitions was 0.023 which corresponded to 23.3 injuries per 1000 minutes of competitions. 45.6 injuries were occurred for each 100 athletes during the course of competitions. The most frequent injuries were mild (68.8%) and critical injuries (24.7%), followed by moderate and severe injuries; 4.3% and 2.1%, respectively. Conclusion: The rate of injury we found was lower than that of western countries. In spite of finding the lower limbs as the most frequent place of injuries in other studies, we found the upper limbs as the most predisposed place of injuries which might be due to difference in the method of combat of Iranian athletes with other athletes.